2011
DOI: 10.1039/c0sm01487g
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of colloidal suspensions confined between a silica microsphere and an air bubble

Abstract: This study contributes to the understanding of the effects of confining surface properties on the interactions within thin liquid films of colloidal nanoparticles. Colloidal probe atomic force microscopy was used for studying the interaction of colloidal nanoparticles between the solid-liquid and air-liquid interfaces. The influence of the surfactant on the surface deformability and on the structuring of the nanoparticles was determined. Therefore, surfactants of different charges, i.e. sodium dodecyl sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 47 publications
3
31
2
Order By: Relevance
“…If there was an effect of surface elasticity, it was manifested as surface force curves that did not increase perpendicularly after the "contact point" but rather deviated from the straight line because of deformation of the surface. 55 This deviation was not observed in the present study even for the thickest film of 12 nm (PAH/ PSS, N = 10, at 0.1 M NaCl), indicating that the effect of surface elasticity was negligible.…”
Section: ■ Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…If there was an effect of surface elasticity, it was manifested as surface force curves that did not increase perpendicularly after the "contact point" but rather deviated from the straight line because of deformation of the surface. 55 This deviation was not observed in the present study even for the thickest film of 12 nm (PAH/ PSS, N = 10, at 0.1 M NaCl), indicating that the effect of surface elasticity was negligible.…”
Section: ■ Discussioncontrasting
confidence: 74%
“…Measurements between a rigid silica microsphere and a bubble reveal that the surface elasticity reduces the amplitude of oscillations. 55 In the present study, however, the thickness of the multilayer in the most cases was less than 6 nm; thus, the effect of surface elasticity was suppressed by the hard silica surface. If there was an effect of surface elasticity, it was manifested as surface force curves that did not increase perpendicularly after the "contact point" but rather deviated from the straight line because of deformation of the surface.…”
Section: ■ Discussionmentioning
confidence: 66%
“…The surface force apparatus (SFA) [62,63] and colloidal-probe AFM (CP-AFM) [52,53] gauge the forces with bending of a calibrated spring. Prominently, micelles [58,[64][65][66][67][68][69] and spherical nanoparticles (particularly SiO 2 [29,52,53,68,[70][71][72]) are among most widely studied model nanofluids for mediating depletion and related structural forces, with nanorods-mediated depletion also measured [60,61].…”
Section: Direct Measurement Of Depletion and Structural Forces Betweementioning
confidence: 99%
“…For Silica dispersions conned in a CP-AFM it has been shown that the structural forces (which corresponds to stratication in foam lms) are an effect of connement. The oscillation period is very robust against changes in elasticity of the surface (uid or solid), 79 surface charge, 80 surface roughness, 81 ionic strength 82 and against (non)presence of surfactants of different charges. 79 On the other hand, these parameters affect the amplitude (strength of ordering) and the decay length (range of ordering).…”
Section: Comparison With Oscillatory Forces Through Polyelectrolyte Smentioning
confidence: 99%